The Relationship between Foreign Direct Investment Inflows of World, Foreign Direct Investment Inflows of Turkey and Types of the Special Economic Zone: Evidence from 1980-2019 - Demet Ozocakli; Bahman Khanalizadeh (Iranian Journal of Finance, 2022)
There are many factors affecting Foreign Direct Investment inflows into the countries. One of them is Special Economic Zones that encourage Foreign Direct Investment inflows and achieve remarkable results in the world. Special Economic Zones are defined in the United Nations Conference on Trade and Development as the regions where production, trade and storage are not limited to time and are exempt from customs and taxes. This study analyzed the relationship between the Foreign Direct Investment inflows of Turkey, the Foreign Direct Investment inflows of the World and the number of the Special Economic Zone types analyzed using the Autoregressive Distributed Lag Method from 1980 to 2019. The results show that Foreign Direct Investment inflows of the World have a positive and significant effect on Foreign Direct Investment inflows Turkey in the long term and the short term. Also, the number of total Special Economic Zone has a positive and significant on the Foreign Direct Investment inflows of Turkey. Foreign Direct Investment inflows of Turkey increase 1.01% and 2.58% in long term and short term, respectively when the increase is 1% in the number of total Special Economic Zone. Moreover in this study, a number of the Special Economic Zone types such as OIZ, TDZ, FZ have been analyzed.